Pengaruh Kualitas Pelayanan dan Kinerja Pegawai Desa terhadap Kepuasan Masyarakat di Desa Dayeuhwangi Kabupaten Majalengka - Parhanudin, Irpan; Halim, Hartanto; Parlina, Yeyen (Jurnal Manajemen dan Administrasi Antartika, 2025)
This study aims to determine the effect of service quality and village employee performance on community satisfaction in Dayeuhwangi Village, Lemahsugih District, Majalengka Regency. This research employed a quantitative method with a sample of 60 respondents collected through questionnaires. The t-test results show that service quality (X1) has a positive and significant effect on community satisfaction (Y), with a t-value of 2.388 > t-table 1.671. Furthermore, village employee performance (X2) also has a significant effect on community satisfaction with a t-value of 3.009 > t-table 1.671. The simultaneous F-test indicates that service quality and village employee performance together significantly influence community satisfaction, with an F-value of 16.798 > F-table 3.159. These findings highlight the importance of improving public service quality and village employee performance to enhance overall community satisfaction in Dayeuhwangi Village.